Dark fermentative biohydrogen production from palm oil mill effluent: operation factors and future progress of biohydrogen energy - Rosman, Fatin Sakinah; Mohd Yusoff, Mohd Zulkhairi; Zakaria @ Mamat, Mohd Rafein; Maeda, Toshinari; Hassan, Mohd Ali (Universiti Putra Malaysia Press, 2020)
Malaysia is one of the largest producers and exporters of palm oil, thus, a large amount of palm oil mill effluent (POME) is generated through this process. POME contributes to environmental pollution if it is not properly treated. This complex effluent consists of colloidal matters and mainly organic components with more than 90% water. Thus, it is useful to be used as a substrate for fermentative processes, including biohydrogen production. Biohydrogen from POME is a renewable source that can potentially serve as an alternative to substitute fossil fuels. The abundance of POME and the rising price of fossil fuels in the global market create a demand for this source of energy. However, the complexity of the substituents in POME makes the optimisation of this effluent as a substrate in dark fermentation a challenge. This review article explores the important parameters that need to be considered for optimal biohydrogen production, such as the bioreactor operational parameters and the microbial consortium. Besides, the potential of metabolic engineering as a tool to overcome the limitations of the microbial strains to metabolise POME for increased biohydrogen production was also reviewed. However, further research and development are needed to increase the biohydrogen yield on par with commercial demand.